Preferences towards international luxury apparels among Generation Y from the perspective of the university students / Mohd Azif Fahmi Dahari and Nurul Adibah Izza Zuhairi - Dahari, Mohd Azif Fahmi; Zuhairi, Nurul Adibah Izza (Faculty of Business and Management, 2016)
This research aims to identify the predictor of consumer preferences in choosing international luxury apparel among generation Y from the perspective of the university students. A total of 150 students took part in this survey. The study found that fashion style has the strongest predictor towards international luxury apparels followed by country of origin. This study is imperative to the marketers to understand the student’s preferences in a part of Peninsular Malaysia. The marketer also could realize the market segmentation and consequently formulate competitive marketing strategies and utilize target market wisely.